2016
DOI: 10.1016/j.cytogfr.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-18 in the pathophysiology of allergic diseases

Abstract: Interleukin (IL)-18 is an IL-1 family cytokine expressed by macrophages, dendritic cells, epithelial cells, and keratinocytes and is implicated in various aspects of both the innate and adaptive immune systems. IL-18 signals similar to IL-1β intracellularly to activate gene transcription. Since its discovery, IL-18 has been demonstrated to play a key role in pathogen defense from helminths and some bacteria. Recently however, evidence has accumulated that IL-18 expression is increased in many presentations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 144 publications
(129 reference statements)
4
32
0
Order By: Relevance
“…These data indicate that eotaxin-1 may not be critical for intestinal eosinophil accumulation when IL-18 expression is locally induced. 17,27,38 These findings are consistent with earlier reports regarding the role for eotaxin-1 in regulating eosinophil homing to the gastrointestinal tract in health and diseases. 1,42,43 Similarly, eotaxin-2 was not found to be induced in Fabpi-IL-18 transgenic mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data indicate that eotaxin-1 may not be critical for intestinal eosinophil accumulation when IL-18 expression is locally induced. 17,27,38 These findings are consistent with earlier reports regarding the role for eotaxin-1 in regulating eosinophil homing to the gastrointestinal tract in health and diseases. 1,42,43 Similarly, eotaxin-2 was not found to be induced in Fabpi-IL-18 transgenic mice.…”
Section: Discussionsupporting
confidence: 92%
“…The current study provides a mechanistic understanding regarding a direct role of IL-18 in promoting eosinophilia in the intestine, and supports our previous findings that IL-18 overexpression promotes EoE. 17,27,38 Notably, several eosinophil-associated gastrointestinal disorders have co-existing peripheral blood eosinophilia. 44,45 These patients have induced levels of IL-18, and we show that IL-18 intestinal transgenic mice had both induced peripheral blood and intestinal eosinophil accumulation.…”
Section: Discussionsupporting
confidence: 88%
“…IL-18 is a pro-inflammatory cytokine that induces IFN-γ production, which is closely related to the pathophysiologic mechanism of allergic respiratory disorders [28]. In the present study, we showed that free plasma IL-18 was elevated in pAR and sAR patients, sAR patients had a decreased IL-18BP/IL-18 ratio (9.7), and free IL-18 correlated well with free IL-18BP in the plasma of both pAR patients and sAR patients, indicating that the imbalance between IL-18 and IL-18BP is likely to be crucial to the development of AR as a molar excess of 10 of IL-18BP over IL-18 is required to decrease a pathological level of 400 pg/ml of IL-18 to a level of a HC subject (40 pg/ml) [11].…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 is a potential pro-inflammatory cytokine. Although the involvement of IL-18 has been implicated in various diseases, especially autoimmune diseases, such as allergy and systemic lupus erythematosus 7 , 21 , only a few studies have demonstrated IL-18 regulation is involved in inflammatory myopathy 22 . We show that HIMF induces IL-18 expression in murine myoblasts through PDK1, which acts as a downstream effector in the PI3K/Akt/c-Jun signaling pathway and has been implicated in the regulation of neutrophil migration.…”
Section: Discussionmentioning
confidence: 99%
“…Under pathological conditions, angiogenesis stimulates vascular endothelial growth factor (VEGF) expression in the smooth muscle cell phenotype 6 . Interleukin-18 (IL-18) is a pro-inflammatory cytokine that belongs to the IL-1 family, and has been identified in autoimmune disorders 7 . High levels of serum IL-18 have been observed in patients with inflammatory myopathy 8 .…”
Section: Introductionmentioning
confidence: 99%